2012
DOI: 10.2174/1874325001206010231
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Intra-Articular Use of Atelocollagen for Enhanced Tissue Repair

Abstract: Collagen is an important biomaterial in intra-articular tissue engineering, but there are unanswered questions about its safety. We hypothesize that the addition of type-I-collagen for primary repair of the Anterior Cruciate Ligament (ACL) might result in a local and systemic reaction in a porcine model after 15 weeks as demonstrated by joint effusion, synovial thickening, elevated intraarticular and systemic leukocyte counts. Further, this reaction might be aggravated by the addition of a platelet con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…[20][21][22][23] Furthermore, other studies stressed the importance of providing a suitable biological environment by adding a collagen matrix sponge [25][26][27][28][29] or PRP to stimulate healing. [30][31][32][33] The literature suggests a mutually inclusive relation between collagen matrix sponge and PRP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22][23] Furthermore, other studies stressed the importance of providing a suitable biological environment by adding a collagen matrix sponge [25][26][27][28][29] or PRP to stimulate healing. [30][31][32][33] The literature suggests a mutually inclusive relation between collagen matrix sponge and PRP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mechanical augmentation, several groups have investigated the role of biologics in primary ACL repair including the use of a collagen scaffold [25][26][27][28][29] and platelet-rich plasma (PRP). [30][31][32][33] Fleming et al 25 reported that augmentation with a bovine collagen scaffold alone did not improve the biomechanical properties of a repaired porcine ACL.…”
Section: Preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The BEAR scaffold softens when blood is added to it, making it conformable to the intra-articular notch and able to fill in the irregular contours of the gap between the torn ligament ends. The scaffold material has been tested in preclinical large animal studies 15,16,22,38 in which the healing ACL was found to have similar mechanical properties to a bone–patellar tendon–bone allograft at 3, 6, and 12 months after surgery. 21,33 In addition, pigs treated with the BEAR scaffold had a significantly lower rate of osteoarthritis than those treated with ACL reconstruction.…”
Section: Methodsmentioning
confidence: 99%
“…Collagen is the connective tissue protein which has a key role in maintaining tissue morphology, and atelocollagen is a highly purified type I collagen obtained following the treatment of pepsin from skin dermis [Magarian et al, 2012]. This atelocollagen is obtained following the removal of telopeptide which is immunologically problematic and is used for a number of purposes such as wound healing, vessel prosthesis, bone substitute and hemostatic agent [Kojima et al, 2007].…”
Section: Discussionmentioning
confidence: 99%